Life cycle energy and GHG emissions of PET recycling change oriented effects. - Shen, Li (The International Journal of Life Cycle Assessment)
Purpose The demand of PET bottles has increased rapidly in the past decades. The purpose of this study is to understand the environmental impact of PET recycling system, in which used bottles are recycled into both fibre and bottles, and to compare the recycling system with single use PET. Methods Consequential LCA modelling was applied to understand four change oriented effects for the recycling system. These include the effect of multiple recycling trips, the effect of changing the share of recycled PET pellets used to make bottles or fibre, the effect of changing the reference system and the effect of introducing bio-based PET. The functional unit of the baseline case was determined as 350 kg of bottles and 650 kg of fibre based on the current market demand of PET. The system boundary is cradle to grave excluding the use phase. We applied the "system expansion" method to open loop recycling. The analysis compares the baseline recycling system, where PET is recycled once, with the reference system, where PET is not recycled. The environmental impacts assessed are non renewable energy use and global warming. Results and discussion The baseline recycling system reduces both impacts by 20 percent when compared to the reference system. Multiple recycling trips can maximally reduce the impacts by 26 percent but the additional savings are negligible after three recycling trips. Bottle to fibre recycling offers more impact reduction than bottle to bottle recycling when more fibre is needed than bottles in a functional unit. The maximal impact reduction of 25 percent can be achieved when all recycled PET pellets are used to make fibre. If the functional unit is reversed, i.e. changed to 650 kg of bottles and 350 kg of fibre, 30 percent of the impact reduction can be achieved. Both impacts can be further reduced when the quantity of the recycled PET is maximised. The bio-based PET recycling system, offers at least 36 percent impact reduction, has the lowest impact among all systems studied. The sensitivity analyses show that the recycled PET content in a recycled bottle is not influential to the overall environmental performance. Conclusions All PET recycling systems in this study show important impact reduction compared to the reference system. The impact savings are around 20-30 percent depends on the configurations of the recycling system. We conclude that the system's environmental impact can be optimised by maximising the amount of recycled PET in the system and by using bio-based polymers.